2013
DOI: 10.1016/j.compstruct.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of fibre composite sandwich structures under short and asymmetrical beam shear tests

Abstract: The behaviour of structural fibre composite sandwich beams made up of glass fibre composite skins and phenolic core material was investigated under three-point short beam and asymmetrical beam shear tests. The effect of the shear span-to-depth ratio (a/D) on the strength and failure behaviour of the composite sandwich beams was examined. The results showed that with increasing a/D ratio, the failure load of the sandwich beam is decreasing. On the contrary, the coupling effect of flexural stresses increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…From an experimental investigation of the sandwich beams at horizontal orientation, Manalo [18] observed a transitional zone for a/d ratios between 3 and 6, where the specimens experienced both shear and bending. In the present study when a/d ≥ 6, the bending failure was observed for the specimens.…”
Section: Effect Of Shear Span-to-depth Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…From an experimental investigation of the sandwich beams at horizontal orientation, Manalo [18] observed a transitional zone for a/d ratios between 3 and 6, where the specimens experienced both shear and bending. In the present study when a/d ≥ 6, the bending failure was observed for the specimens.…”
Section: Effect Of Shear Span-to-depth Ratiomentioning
confidence: 99%
“…This failure mechanism needs further investigation. In many circumstances, researchers have found the differences between experimental and theoretical failure loads of sandwich beams up to 20% [19], 21% [31], 30% [37], 34% [18], and even up to 100% [7]. Therefore, further investigation is necessary to establish better theoretical models that can capture the insight into the response of the sandwich beams.…”
Section: Comparison Between Calculated and Actual Failure Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these drawbacks, alternate methods should be used to measure the shear modulus and shear strength values of XPS. The asymmetric four-point bending (AFPB) test, which is regarded as an application of the Iosipescu shear test, could help to overcome these drawbacks [21][22][23][24][25][26]. The AFPB test is more advantageous than the aforementioned shear tests in that it does not require an apparatus specially designed for the test but that for the universal four-point bending test; therefore, the test can be conducted easily and conveniently.…”
Section: Introductionmentioning
confidence: 99%
“…At the location of loading, the maximum bending moment and shear forces exist. Manalo [36] and Awad et al [37] highlighted that for composite beams with a shear span-to-depth ratio (a/d) less than 4.5, failure will occur due to a combined effect of shear and flexural stress. In the current study, the tested beams have an a/d = 4.2.…”
Section: Failure Modementioning
confidence: 99%